Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Masalah Matematika Open-Ended Berbantuan Mathigon Ditinjau dari Kemampuan Matematika - Mustika Maharani Jarkoni; Tatag Yuli Eko Siswono (Universitas Negeri Surabaya, 2026)
Creative thinking skills play an important role in enabling students to generate various ideas and strategies when solving open-ended mathematics problems. This study aims to describe students' creative thinking skills in solving open-ended mathematics problems with the help of Mathigon, based on their mathematical ability levels (high, medium, and low). This study employs a qualitative case study approach involving six students selected based on the categories of mathematical ability, adaptability to digital technology, and fluency in oral communication. Data were collected through a mathematical ability test, Mathigon-based problem-solving tasks, and in-depth interviews. Data analysis was conducted based on creative thinking indicators: fluency, flexibility, and novelty. The results showed that students with high mathematical ability met all indicators. In contrast, students with medium mathematical ability showed varying results (one student met all indicators, another student only showed fluency). Students with low mathematical ability did not show flexibility but showed potential in fluency and novelty. This study indicates that Mathigon, as an interactive medium, supports the development of students' creative thinking skills in solving open-ended mathematics problems at various ability levels.